A healthy you : boost your energy, live cleaner, and look and feel younger everyday - Alt, Carol, 1960-; Steiber, Jocelyn (Dey St., an imprint of William Morrow Publishers, 2015)
The supermodel and TV host culls the best advice from her favorite doctors, fitness gurus, dietitians, and experts to present practical advice, proven tips, recipes, products, and regimens, from raw eating to chemical-free cosmetics, for living a cleaner, greener lifestyle.